Contestations and Contradictions in the Argentine Redes de Trueque - Georgina M. Gómez; Joop de Wit (Revue de la Régulation)
Complementary and Community Currency Systems are studied as schemes of monetary contestation, following the assumption that the rejection of official money implies a micro-political act of resistance to the government, the globalised economic system and the instruments of control that sustain them. This research seeks to trace the diverse interpretations of the principle of monetary contestation in the daily economic practices of the Argentine complementary currency systems. The different political visions within the Redes de Trueque resulted in vertical and horizontal divides among the actors. Only some of them proposed a project of monetary contestation while a second group sustained a desire of resilience and conservation of their lifestyle, and a third one was driven by pragmatism and survival during the economic demise. The reaction of the government, especially at the local level, was supportive of the projects of resilience and pragmatism. For local governments and informal political brokers, the initiatives were consistent with their own political goals, so they further disseminated the scheme. In conclusion, monetary contestation is only one of the various aspirations of CCS participants.